Exchanging our country marks : the transformation of African identities in the colonial and antebellum South - Gomez, Michael A., 1955- (University of North Carolina Press, 1998)
"After discussing specific ethnic groups in Africa, Gomez follows their movement to North America, where they tended to be amassd in recognizable concentrations within individual colonies."